CONSIDERATIONS REGARDING AIR POLLUTION AND HEALTH RISKS - Daniela CÎRŢÎNĂ (Fiabilitate şi Durabilitate)
Atmospheric pollutants are a very wide range of substances that differ from one another in terms of their chemical properties and their effects on humans or the environment. The toxic potential of gases and vapors in achieving a higher or lower concentration and in achieving a particular receptivity depends on a number of factors that are related to the particularities of the toxic, the external environment and the exposed organism. In this paper we present aspects related to the air pollution, the health effects due to exposure to atmospheric pollutants, the factors that depend on the toxicity of toxic gases and vapors and the risk of illness due to the main categories of atmospheric pollutants.